TRANSLATION STRATEGIES IN TRANSLATING THE ACEHNESE PROVERBS INTO BAHASA INDONESIA - Bungsu Keumala Sari; Amin Saragih; Zainuddin Zainuddin (LINGUISTIK TERAPAN, 2019)
The reserach dealt with Acehnese proverbs with the aims of this study were to (1) toinvestigate kinds of translation strategies in translating the Acehnese proverbs into Bahasa Indonesia, (2) to investigate Acehnese proverbs realized in its translationinto Bahasa Indonesia, (3) to describe the translation strategies applied in the ways they are. The research was conducted by using qualitative descriptive design. The data of this study were Acehnese proverbs and there were translated into Bahasa Indonesia by Hasjim M.K. at all (1977) taken from the book entitle “Peribahasa Aceh”. The results of this study showed that (1) There were three kinds of translation strategies in translating the Acehnese proverbs into Bahasa Indonesia namely exact equivalent, near equivalent, and literal meaning,  (2) In realization of Acehnese proverbs there were three ways in translating proverbs namely the words following the proverb could be introduced as the meaning of the proverb, it can be replaced with an equivalent local proverb, and its non-figurative meaning could be stated straight forwardly,  (3) In translating Acehnese proverbs, the translators need to know all aspects of cultural background of both languages.Key words: Translation, Strategies, Proverbs